Checklist of the Inland Fishes of Louisiana - Michael H Doosey; Henry L Bart Jr.; Kyle R Piller (Southeastern Fishes Council Proceedings, 2021)
Since the publication of Freshwater Fishes of Louisiana (Douglas, 1974) and a revised checklist (Douglas and Jordan, 2002), much has changed regarding knowledge of inland fishes in the state. An updated reference on Louisiana’s inland and coastal fishes is long overdue. Inland waters of Louisiana are home to at least 224 species (165 primarily freshwater, 28 primarily marine, and 31 euryhaline or diadromous) in 45 families. This checklist is based on a compilation of fish collections records in Louisiana from 19 data providers in the Fishnet2 network (www.fishnet2.net). The checklist has grown because of descriptions of three new species, new distribution records of both native and non-native species, and the addition numerous of marine species that are known to enter freshwaters in Louisiana.
Keywords: freshwater; brackish; marine; ichthyofauna